Waste management education in coastal communities: evaluating the impact of visual campaigns and local engagement - RA. Ummu Kulsum (Indonesian Journal of Applied Community Research, 2026)
Background: Coastal communities in Indonesia continue to face persistent waste management challenges due to high plastic consumption, limited infrastructure, and low environmental awareness, particularly in fisheries-based settlements where daily economic activities generate concentrated waste streams. Objective: This program aimed to enhance environmental awareness and initiate behavioral change in household and coastal waste management through visual campaigns and participatory community engagement in Puger Kulon, Jember Regency. Method: A participatory implementation design was applied, involving contextual planning, visual educational media, community socialization, youth engagement, and short-term monitoring and evaluation. Results: The program reached approximately three-quarters of targeted households, increased awareness of plastic waste impacts, and stimulated early behavioral changes, including basic waste separation by about half of participants and reduced waste accumulation in key coastal areas, alongside emerging waste-conscious social norms. Implication: These findings suggest that visually driven, community-based interventions can effectively initiate environmental awareness and behavior change, although long-term sustainability requires stronger infrastructural and institutional support. Novelty: The program introduces an integrated model combining place-based visual communication, participatory engagement, and light mentoring as a practical and replicable approach for improving coastal waste governance.